2007
DOI: 10.1152/physiolgenomics.00178.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postnatal hepatic gene expression profiles of two pig breeds differing in body composition: insight into pathways of metabolic regulation

Abstract: The liver plays a central role in the regulation of the metabolic status, partitioning of nutrients, and expenditure of energy. To gain insight into hepatic metabolic pathways and key transcripts affecting traits related to body composition, liver expression profiles were compared of pigs of two breeds, the obese German Landrace (DL) and the lean Pietrain (Pi). Porcine oligonucleotide microarray were hybridized with liver cRNAs obtained at peripubertal age (180 days of age) and prenatal stages (35, 63, and 91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 60 publications
5
29
0
2
Order By: Relevance
“…Ghazalpour et al ( 21 ) found that the mapping resolution for eQTL was signifi cantly greater in the outbred population than in F2 intercrosses and showed how this precise mapping could resolve previously identifi ed loci (in F2 intercross studies), which affect many different transcript levels (known as eQTL 'hotspots), into distinct positively correlated with FA, whereas genes with negative correlation were associated with cellular development, cellular growth, and proliferation. These fi ndings were in agreement with our previous conclusion that the genetic differences between obese and lean pig breeds were associated with upregulation of lipid metabolic pathways in obese pigs and upregulation of cell growth and/or maintenance and cell proliferation pathways in lean pigs ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…Ghazalpour et al ( 21 ) found that the mapping resolution for eQTL was signifi cantly greater in the outbred population than in F2 intercrosses and showed how this precise mapping could resolve previously identifi ed loci (in F2 intercross studies), which affect many different transcript levels (known as eQTL 'hotspots), into distinct positively correlated with FA, whereas genes with negative correlation were associated with cellular development, cellular growth, and proliferation. These fi ndings were in agreement with our previous conclusion that the genetic differences between obese and lean pig breeds were associated with upregulation of lipid metabolic pathways in obese pigs and upregulation of cell growth and/or maintenance and cell proliferation pathways in lean pigs ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…Through its key function in lipogenesis, FASN may play a crucial role in determining the variability in weight of abdominal adipose tissue. Moreover, it has been found to be involved in lipid metabolism pathways in studies of pre-and postnatal hepatic gene expression profiles of two pig breeds differing in body composition (Ponsuksili et al, 2007). The present study found that FASN regulates fatty acid biosynthesis, lipid biosynthesis and fatty acid synthase activity.…”
Section: Candidate Genes For Fat Metabolismsupporting
confidence: 58%
“…It is known that each fat depot has a different function with regard to lipid biosynthesis or lipid storage (Mourot, Kouba, & Peiniau, 1995;O´Hea & Leveille, 1969). In pigs, lipogenesis occurs predominantly in subcutaneous fat, although the liver also has input in this process (Ponsuksili, Murani, Walz, Schwerin, & Wimmers, 2007). Furthermore, a number of hepatic biomarkers have been shown to be associated with IMF and subcutaneous fat content (Fan, Du, & Rothschild, 2010;Jiang, Li, & Yang, 2006).…”
Section: Discussionmentioning
confidence: 99%